The level of knowledge of health-oriented physical activity among post-secondary students - Nowak, Paweł F. (Polish Journal of Public Health, 2010)
Aim. The main objective of this research is a study of the opinions expressed by adolescents, who are finishing the fourth education level, on the co-relations between physical activity and health, as well as an evaluation of their level of knowledge about the types of pro-health physical activities. Material and methods. The research covered 1,544 pupils from 21 post-secondary schools, in their last year of education. The method of the diagnostic sounding was used to this research. An anonymous opinion poll was applied as the research technique. Conclusion. The examined adolescents have a satisfactory level of knowledge on the positive relations between physical activity and health. What could be worrying, is the fact, that physical education classes have low esteem when it comes to their impact on health. The students’ knowledge of the types of health-oriented physical activities is low.